eDNA Metabarcoding Reveals the Species–Area Relationship of Amphibians on the Zhoushan Archipelago - Wenhao Li; Xianglei Hou; Yunlong Zhu; Jiacong Du; Chunxia Xu; Jingyuan Yang; Yiming Li (Animals, 2024)
The species–area relationship is important for understanding species diversity patterns at spatial scales, but few studies have examined the relationship using environmental DNA (eDNA) techniques. We investigated amphibian diversity on 21 islands of the Zhoushan Archipelago and nearby mainland areas in China using the combination of eDNA metabarcoding and the traditional line transect method (TLTM) and identified the species–area relationship for amphibians on the islands. The mean detection probability of eDNA is 0.54, while the mean detection probability of TLTM is 0.24. The eDNA metabarcoding detected eight amphibian species on the islands and nine species in the mainland areas, compared with seven species on the islands and nine species in the mainland areas that were identified by TLTM. Amphibian richness on the islands increased with island area and habitat diversity. The species–area relationship for amphibians in the archipelago was formulated as the power function (S = 0.47A0.21) or exponential function (S = 2.59 + 2.41 (logA)). Our results suggested that eDNA metabarcoding is more sensitive for the detection of amphibian species. The combined use of eDNA metabarcoding and the traditional line transect method may optimize the survey results for amphibians.